Factors Affecting Firm Value of Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) - Reni Febriani; Supriyanto (TEMA, 2024)
The primary components of this research are the DER Ratio, Current Ratio (CR), ROE Ratio, and TATO Ratio. From 2019 to 2022, data from 185 manufacturing companies listed on the Indonesia Stock Exchange (IDX) were analyzed using a quantitative approach. This research provides an analysis of factors that influence firm value in their operations. The results show that TATO and CR have an insignificant influence on firm value, whereas DER and ROE have a significant impact. Companies that manage their debt and equity capital well tend to be more attractive to investors, as high ROE indicates good profitability, while an appropriate DER indicates effective debt management. This research is useful for investors in selecting more important factors to consider when assessing investment potential in manufacturing companies, as well as for companies in designing strategies to enhance firm value.